9. Dual-Platform Products (PC and Mac) - Feist, David; Belyk, Diane (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2002)
Most of the other reports in this series have featured collaborative tools that were designed for use on PC-compatible platforms, and tested by our evaluation team on these platforms exclusively. This report reviews four integrated software products ensuring “interoperability” between the two major computing systems, PC-compatible and Macintosh. The products are compared in terms of their different levels of interoperability and complexity, as defined by the American Society for Training & Development (ASTD).